Terminal flower 1(TFL1) homolog genes in monocots. - Abdullah, Mohd Puad; Ab Shukor, Nor Aini; Tahery, Yaghoob; B., Norlia; Kafilzadeh, Farshid (EuroJournals Publishing, 2009)
Terminal flower1 (TFL1) is a key gene in charge of flowering time in Arabidopsis thaliana. It belongs to a family of phosphatidyl ethanolamine binding protein domain (PEBP). The main issues addressed in this paper are current advances in TFL1 homologs isolated from the monocot plants include rice (Oryza sativa) and ryegrass (Lolium perenne). Taking advantage of previous studies of cloning, in this review we have evaluated function of these genes in regulating flowering time as well as the effect of altered expression of these genes. It will then discuss or address places or parts of these plants where these genes express. Additionally, structural and functional relationships between them are compared.